Correlações entre as propriedades de transportes, térmica e a morfologia de filmes de blendas de pectina de maçã/hidrocoloide da semente da chia - Silva, Ingrid Souza Vieira da (2020)
In this work, different formulations of polymeric blends were studied with variations of apple pectin and hydrocolloid percentages obtained from chia seeds (Salvia hispanica L.), together with additives (glycerol and glutaraldehyde). For the compositions of these formulations, a multivariate design was used, which allows the contents of both matrices and additives to vary concurrently. The samples of polymeric blends were obtained from the casting methodology, and submitted to the tensile test for identification based on the mechanical properties of the most suitable formulations studied, in relation to pure matrices. Then, based on the choice of the best formulations, a second plan was prepared, in which there was a progressive decrease in the glutaraldehyde contents. The procedure was similar to that carried out for the first planning. From the point of view of compatibility, all formulations were compatible, since there was an improvement in the results of the investigated property. The additives significantly altered the mechanical properties, resulting in a decrease in stiffness, and an increase in terms of deformation, but also especially in relation to glutaraldehyde there were changes in the extension about the crosslinking process, more evident in formulations with higher content of this additive, because, in these formulations there was an increase in the swelling content, a decrease in the gel content (insoluble content) after aqueous extraction, a decrease in the polar component of the surface energy, an increase in relation to the glass transition temperature values. From the morphological point of view, the volumetric fraction of apple pectin contributed to changes in the transport properties of water vapor, minimizing them, which becomes interesting with a view to applicability as food packaging. The formulations did not show cytotoxicity, even with high levels of glutaraldehyde. In addition, blends formulations have an antioxidant potential, estimated at approximately 60%, mainly attributed to the contribution of the chia hydrocolloid matrix. The sorption isotherms provided answers about the high sensitivity of the samples, regardless of the formulation analyzed, in relation to the water activity (aw) of the medium. Within the conditions of analysis, the formation of clusters of water molecules was maximized above aw 0.7. The data of permeation to water vapors allowed making correlations on the miscibility of the system, in lower values of volumetric fraction of apple pectin, and immiscibility for higher values, with good fit for the Maxwell model, considering the spherical geometry of this matrix. The XRD diffractograms revealed that all samples have a characteristic profile of semicrystalline materials. The formation of clusters altered the thermal properties of the samples, narrowing the endotherm profile and displacement of the thermal event to very high temperatures, whose changes were attributed to the removal of free water molecules (clusters), already when in a favorable environment the formation of agglomerates occurred an enlargement of the endotherm. A more suitable formulation was chosen and used to estimate the shelf life of the samples, based on the results obtained with the sorption isotherm, and permeation to water vapors. Thus, the simulated tests within the application potential were satisfactory and provided support for further investigations, even within the area of polymeric materials from renewable sources.